1995
DOI: 10.1001/archpsyc.1995.03950130042005
|View full text |Cite
|
Sign up to set email alerts
|

Adoption Study Demonstrating Two Genetic Pathways to Drug Abuse

Abstract: This study confirms the model of two independent genetic factors involved in drug abuse/dependence and previous findings that disturbed adoptive parents are associated with adoptee drug abuse/dependency.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

13
166
2
4

Year Published

1995
1995
2012
2012

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 315 publications
(186 citation statements)
references
References 29 publications
13
166
2
4
Order By: Relevance
“…In a sample of male and female adoptees combined (Cadoret et al, 1986), and a sample of male adoptees only (Cadoret et al, 1995), evidence of a direct as well as a indirect genetic pathway to drug abuse was reported. However, in a sample of female adoptees only , support for only the indirect path was found, suggesting the possibility of gender-specific biological influences.…”
Section: Gender Differencesmentioning
confidence: 99%
See 1 more Smart Citation
“…In a sample of male and female adoptees combined (Cadoret et al, 1986), and a sample of male adoptees only (Cadoret et al, 1995), evidence of a direct as well as a indirect genetic pathway to drug abuse was reported. However, in a sample of female adoptees only , support for only the indirect path was found, suggesting the possibility of gender-specific biological influences.…”
Section: Gender Differencesmentioning
confidence: 99%
“…Cadoret and co-workers (Cadoret et al, 1986(Cadoret et al, , 1995 have reported evidence of two genetic pathways to drug abuse: a direct path leading from alcohol abuse or dependence in the biological parent to drug abuse in the adoptee, and an indirect path from antisocial behavior in biologic relatives to antisocial behavior in adoptee to adoptee drug abuse.…”
Section: Relation To Other Studiesmentioning
confidence: 99%
“…Family influences on children's early alcohol and drug use range from biological transmission of vulnerability to ineffective parenting. Although some evidence of direct heritable linkages exists for substance use [22][23][24][25], the link is more tenuous than that for related conduct disorder and antisocial behavior [26]. Regardless of heritable predispositions for problem behaviors, family contexts serve to buffer or to incubate their expression [27][28][29].…”
Section: Maternal Psychopathology and Child Outcomesmentioning
confidence: 99%
“…Adoption studies suggest that some of the familial patterns are genetically mediated. Individuals adopted from substance-abusing parents are more likely to become substance abusers than the others raised in identical environmentals (Cadoret et al 1986(Cadoret et al , 1995.…”
Section: Genetic Contributions To Human Substance Abuse Vulnerabilitymentioning
confidence: 99%